Myeloma associated amyloidosis presenting as subacute liver failure. Issue 969 (5th July 2006) - Cross, T J S; Wendon, J A; Quaglia, A; Salisbury, J R; Heneghan, M A; Harrison, P M
Abstract : Multiple myeloma related amyloidosis is rare and its presentation with subacute liver failure (SALF) has not been reported. A case is described of a 46 year old woman presenting with a six week history of nausea, abdominal pain, and jaundice. Routine tests failed to establish a cause. Computed tomography showed a small volume liver consistent with SALF. Emergency liver transplantation was not undertaken because of the suspicion of underlying malignancy. At necropsy, liver biopsy showed amyloid deposition and bone marrow biopsy showed multiple myeloma. Thus, amyloidosis should be added to the list of potential causes of SALF.